Community and autonomy: Institutions, policies and legitimacy in multilevel Europe - Fritz W. Scharpf (Campus Verlag, 2010)
Since the mid-1980s, Fritz W. Scharpf's work has been concerned with the evolution of the multilevel European polity and its impact on the effectiveness and legitimacy of democratic government in Europe. This volume begins with the oft-cited essay arguing that Europe's problem solving capacity was constrained by a "joint decision trap." Subsequent analyses distinguish between effective policies promoting "negative integration" and the greater difficulties of "positive integration" which, in turn, correspond to the institutional conditions of "non-political" (judicial) and "political" (legislative) action at the European level. Drawing on these insights, the most recent contributions focus on the asymmetric impact of European law on the institutions and policy legacies of EU member states and on the implications of these asymmetries for the democratic legitimacy of governing at national and European levels. – – Seit Mitte der 1980er Jahre beobachtet Fritz W. Scharpf die Entwicklung der Effektivität und Legitimität europäischer Mehrebenenpolitik. Zu Beginn der hier versammelten Aufsätze steht die Vermutung, die "Politikverflechtungsfalle" beschränke generell die Problemlösungsfähigkeit europäischer Politik. Später betont Scharpf die Asymmetrie zwischen wirksamer "negativer" und schwacher "positiver Integration". Er benennt aber auch die Bereiche, in denen effektive europäische Politik erwartet werden kann oder ausgeschlossen scheint. Scharpfs Blick richtet sich auf die institutionellen Bedingungen, welche die Rechtsetzung und Politikgestaltung begünstigen und zugleich politisches Handeln auf der europäischen Ebene behindern. Nicht zuletzt betrachtet er die Rückwirkungen des EU-Rechts auf die Institutionen und Politiktraditionen der Mitgliedsstaaten.
Keywords: 320